‘DEEP ECOLOGY’ APLIKASI ETIS MANUSIA DALAM BERELASI DENGAN LINGKUNGAN HIDUP - Dian Nanlohy (IAKN Ambon, 2020)
This paper provides an explanation regarding the development of Environmental Ethics relating to a new lifestyle or lifestyle that not only concerns individuals, but also the culture of society as a whole. Human awareness of ecological crises or environmental damage and planet earth generally gives birth to ecological ethical theories which are generally referred to as 'ecocentric ethics'. And through this paper, it is hoped that the current environmental crisis can be resolved by changing the perspective and behavior of humans towards nature fundamentally and radically.